Объяснение:
1 . б) 3(cosx)² - cosx - 2 = 0 ; gffgrthtyu76788786
заміна t = cosx , | t | ≤ 1` ;
3t² - t - 2 = 0 ; D = 25 > 0 ; t = - 2/3 ; t = 1 ;
cosx = 1 ; або cosx = - 2/3 ;
x = 2πn , nЄ Z ; x = ± ( π - arccos2/3 ) + 2πn , nЄ Z .
В - дь : x = 2πn , nЄ Z ; x = ± ( π - arccos2/3 ) + 2πn , nЄ Z .
в) 4(sinx)² + 12sinxcosx = 0 ;
4sinx(sinx + 3cosx ) = 0 ;
sinx = 0 ; або sinx + 3cosx = 0 ;
x = πn , nЄ Z ; sinx = - 3cosx ; │: cosx ≠ 0
tgx = - 3 ;
x = - arctg3 + πn , nЄ Z .
В - дь : x = πn , nЄ Z ; x = - arctg3 + πn , nЄ Z .
=95/70-63/70=32/70=16/35
2.4÷16/35=2 2/5÷16/35=
=12/5÷16/35=12/5×35/16=21/4=
=5 1/4=5.25